Natural Resources Utilization Pattern: A Study in Kangra District of Himachal Pradesh - Dhimam, Pallavi; Pathania, M S (Annals of Arid Zone, 2016)
The study on natural resources utilization pattern of Kangra district of Himachal pradesh have clearly brought out that the analysis of different categories of lands did not show much change over time periods. Increase was observed in the land put to non-agricultural uses. The barren land showed a decreasing trend. The net sown area has almost remained constant. Rice, wheat and maize were the three prominent crops of study area. The share of area under barley, pulses and oilseed was less and decrease over time and found that there was very high increase in vegetables during the period. The highest share of irrigated area was observed under potato followed by vegetables and paddy. Irrigated area under pulses and oilseed was very less and varied between 2 to 12% in different years. The Kuhls and lift irrigation were the two prominent sources of irrigation. Kuhls met the 81% of irrigation requirement in the district. Per cent increase in production and productivity was found in rice, wheat, potato and vegetables. The analysis of compound growth rate had shown that higher increase in production was in wheat (14.9% per annum) followed by vegetables (12% annum). Maximum positive significant growth rate was observed in case of present fallow land (1.81% per annum) and maximum negative significant growth rate was observed in case of barren land (4.71% per annum). The total gross cropped area and area had shown more than once showed negative rate of growth in the district. Maximum declining in area was observed in pulses (19% per annum), followed by barley and oilseed. Maximum positive growth was noticed in vegetables, wheat and paddy in the district.